Fire history in the Araucaria araucana forests of Argentina: Human and climate influences - Mundo, Ignacio Alberto (2012)
Little is known about drivers and trends of historic fire regimes in the Araucaria araucana forests of south-western Argentina. Fire history in these forests was reconstructed by the analysis of 246 fire-scarred partial cross-sections from this fire-resistant tree collected at 10 sites in Neuquén, northern Patagonia. Fire chronologies showed an increase in fire occurrence during the nineteenth century and a sharp decrease since the early twentieth century. The creation of Lanín National Park in 1937, the change in human activities, and the active suppression of wildfires led to a significant increase in mean fire intervals since 1930. In addition to these multidecadal to centennial scale drives of fire frequency, interannual variability in wildfire activity was associated with El Niño-Southern Oscillation. Years of widespread fire are related to negative departures of both Niño 3.4 and Pacific Decadal Oscillation indexes (i.e. La Niña conditions), as well as coincident phases of positive Southern Annular Mode and La Niña events. Temporal variations in the Araucaria fire history in Argentina clearly show the combined effect of human and climate influences on fire regimes. A comparison with previous fire history studies in the Araucaria forests of Chile reveals substantial differences related to differences in human activities on both sides of the Andes and the earlier implementation of protected areas in Argentina.